2015
DOI: 10.1021/jp511544c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Field-Induced Quenching in Poly(p-phenylene vinylene) Polymers and Oligomers

Abstract: Field-induced fluorescence quenching of poly(p-phenylene vinylene) (PPV) oligomers due to nonradiative relaxation through free electron-hole pair (FEHP) states is modeled using singles configuration interaction computations with the intermediate neglect of differential overlap Hamiltonian. The computations find FEHP states with energies that drop linearly with applied field and undergo avoided crossings with the fluorescent state. The coupling between the FEHP and fluorescent state, computed for multiple FEHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Since the excitation in the E-PL measurements was done at the wavelengths where the field-induced change in absorption intensity was negligible, the field-induced quenching results from the field-induced decrease of the fluorescence quantum yield, as already mentioned. 31,44 The fact that the total absorption intensity of the lowest absorption band is not affected by F indicates that the radiative decay rate is not affected by F. As the origin of the field-induced change in emission quantum yield, therefore, the following two possibilities can be considered: (1) the nonradiative decay rate at the emitting state is affected by F; (2) the population yield of the emitting state following photoexcitation is affected by F. The measurements of the PL decay profiles in the presence and absence of electric field can solve the above problem.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Since the excitation in the E-PL measurements was done at the wavelengths where the field-induced change in absorption intensity was negligible, the field-induced quenching results from the field-induced decrease of the fluorescence quantum yield, as already mentioned. 31,44 The fact that the total absorption intensity of the lowest absorption band is not affected by F indicates that the radiative decay rate is not affected by F. As the origin of the field-induced change in emission quantum yield, therefore, the following two possibilities can be considered: (1) the nonradiative decay rate at the emitting state is affected by F; (2) the population yield of the emitting state following photoexcitation is affected by F. The measurements of the PL decay profiles in the presence and absence of electric field can solve the above problem.…”
Section: ■ Discussionmentioning
confidence: 99%
“…External electric-field effects on absorption and photoluminescence (PL) spectra have been extensively used to examine electronic structure as well as excited-state dynamics, following photoexcitation including electron and/or hole mobility. Recently, E-A spectroscopic study of (C 4 H 9 NH 3 ) 2 Pbl 4 was reported by Amerling et al who fabricated the transparent thin film of (C 4 H 9 NH 3 ) 2 Pbl 4 on quartz substrate decorated with gold interdigitated electrodes and applied electric fields parallel to the inorganic [PbI 6 ] 4– sheets. They focused mainly to the band-edge region to estimate the binding energy of the exciton and insisted as the first evidence for Franz–Keldysh (F–K) oscillation in (C 4 H 9 NH 3 ) 2 Pbl 4 quantum well.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Previous studies performed on phenylene-vinylenes have proved good achievements performed using this procedure. 24,27,[50][51][52][53] Specific treatments of decoherence 54 and trivial unavoided crossings were considered. 55 While experimental studies were performed using chloroform as a solvent, 19 our preliminary tests using chloroform as an implicit solvent do not reveal significant changes in the relative energies between states; hence, all our simulations have been performed in a vacuum.…”
Section: Methodsmentioning
confidence: 99%